2008
DOI: 10.1186/1471-2350-9-76
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between serotonin transporter gene polymorphism 5-HTTLPR and smoking among Polish population: a case-control study

Abstract: Background: A better understanding of the genetic determinants of tobacco smoking might help in developing more effective cessation therapies, tailored to smokers' genotype. Insertion/deletion polymorphism in the promoter region of the serotonin transporter gene (5-HTTLPR) has been linked to vulnerability to smoking and ability to quit. We aimed to determine whether 5-HTTLPR genotype is associated with smoking behavior in Caucasians from Northern Poland and to investigate other risk factors for tobacco smoking. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
(51 reference statements)
1
9
0
2
Order By: Relevance
“…In 2008, Sieminska et al [32] were not so selective in recruiting smoker individuals, similarly to Nilsson et al [36] who selected daily or occasional smokers. These types of selection may not recruit those smokers that really have a high degree of dependence and are probably those that really suffer from great genetic susceptibility.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In 2008, Sieminska et al [32] were not so selective in recruiting smoker individuals, similarly to Nilsson et al [36] who selected daily or occasional smokers. These types of selection may not recruit those smokers that really have a high degree of dependence and are probably those that really suffer from great genetic susceptibility.…”
Section: Discussionmentioning
confidence: 91%
“…However, some research, such as the pioneer study by Lerman et al [31], did not report association of smoking behavior with the 5-HTTLPR polymorphism [32][33][34].…”
Section: Discussionmentioning
confidence: 97%
“…The relationship between the 5HTT gene and dependence has been widely studied and the short allele of 5HT system has received considerable attention in addiction. Although the findings remain equivocal in other studies, it showed no evidence for association [24,27,28], while in some studies a positive association was found [6,29]. Some recent evidences indicate that the association of addiction with short allele may be different in men and women, while it was observed to be homozygote for the short allele among males, this was heterozygote among women.…”
Section: Discussionmentioning
confidence: 40%
“…Some studies found the evidence for the role of serotonin in autism and addiction. In contrast with these findings, some other studies failed to demonstrate an association between serotonin transporter gene polymorphism and the personality traits at risk for substance abuse and autism [6,10,23,24]. Based on the above-mentioned reasons, the present study designed to investigate the hypothesis that the frequency of the "low activity" S allele might be higher in the opioid addiction, when compared with non-addiction people.…”
Section: Introductionmentioning
confidence: 72%
“…Araştırmacılar bunun ana nedeninin çalışmalarda ki örneklerin heterojenitesinden kaynaklanan kısıtlılıklar olduğunu ifade etmişlerdir. [50][51] …”
Section: Serotonerjik Sistem Ile İlgili Genlerunclassified